Optimal design and simulation analysis of millimeter wave MIMO radar - He, Xiaoyu (Nanyang Technological University, 2022)
In the automation industry, radar has evolved into the midstream front pillar of Advanced Driver Assistance Systems (ADAS), with standalone radar being utilized for advanced cruise control gain or additional radar system gain. FMCW radar, unlike conventional CW radar, estimates the distance to a target by emitting waveforms of varying frequencies periodically. Nevertheless, the multiple-input multiple-output (MIMO) technology can enhance angular resolution while reducing the number of antenna elements used. Therefore, the optimal design of mmWave radar with the advanced MIMO (multiple-input multiple-output) technology is a practical topic worth discussing.